Moderating role of gender in relationships between personal, maternal, and contextual factors with adjustments among adolescents in Mashhad, Iran - Sabour Esmaeili, Nooshin (2012)
In recent decades divorce has become considerably more common. It is a life crisis for almost all families who experience it. The high number of divorced families over the past decade has created a vast amount of attention on the effects of divorce. The relationships between maternal and contextual factors with adolescents’ adjustment in divorced families have been established. However, much is to be understood on what factors moderate these relationships. It has received little attention in Iran. To address this paucity, the present study was conducted to study the moderating role of gender in the relationships between maternal and contextual factors with adjustment among adolescents in divorced families. Thus, the present study is essential and necessary. The main purpose of this study was to determine the moderating role of gender in relationships between maternal (maternal distress, economic hardship) and contextual (post-divorce parental conflict, parent-child relationship) factors with adolescents’ adjustments (self-esteem, delinquency and academic achievement) in divorced families in Mashhad, Iran. This study is a quantitative study and utilized a correlation research design. Respondents of the study consisted of 800 female and male high school students of divorced families aged between 15 and 18 years and their mothers whom were identified by probability proportional to size sampling technique. Data were collected using self-administered questionnaire. The questionnaire consisted of Centre for Epidemiology Studies Depression Scale (CES-D), Economic Hardship Questionnaire, Post-divorce Parental Conflict Scale, Parent-Child Relationship scale, Self-Esteem Scale and Youth Self-Report Scale. Academic achievement was measured by students’ CGPA. All the instruments used in this study were highly reliable. Descriptive, bivariate and multivariate statistics were used in data analysis. The findings of the Pearson correlation analyses showed that maternal (maternal distress, economic hardship) and contextual (post-divorce parental conflict, parentchild relationship) factors were significantly related to adolescents’ adjustments (self-esteem, delinquency and academic achievement). The result of t-test showed that male respondents had significantly lower self-esteem and academic achievement and higher delinquency than female respondents. The hierarchical regression.